Methodology of instrumental observations of deformations and technical condition of buildings and structures - Sailygarayeva, М.А.; Nyssanbay, Н.Н.; Baigurin, Ж.Д. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The article is aimed at solving the problems of creating an effective survey network for conducting instrumental observations of the deformation processes of a building in the conditions of a foothill area with an energy class of earth's surface movements equal to 4-5. Periodic observations of the technical condition contribute to the timely identification of critical deviations in the structural elements of the building and ensure the safe operation of the structure. Around the object under study, a methodology has been proposed for constructing a geodetic network with the laying of a class III leveling course in order to conduct periodic observations of the sedimentary movements of the building foundation and determine the quantitative values of the sediments, taking into account the territorial location, engineering-geological conditions, seismicity of the area and the influence of the external environment.